On the Manufacture of Fertilizer from Tennessee Phosphate Rock by the Blast Furnace Process : Experiments Carried out from October, 1933, to April, 1934 - Royster, P. H. (Percy Hoke); Hignett, Travis P. (Travis Porter); Bowe, Leon Evans; Lansdon, H. I.; Clark, K. G.; Southard, J. C. (1934)
Technical report recounting the experiments carried out between October 1933 and April 1934 by the United States Bureau of Chemistry on behalf of the Tennessee Valley Authority. The experiments, generally speaking, investigated the maximization of thermal efficiency for phosphate smelting furnaces. The primary experimental finding indicates that commercial phosphate blast furnaces for fertilizer manufacture should reach a temperature of at least 2300 degrees Fahrenheit in the smelting process. The work includes four black-and-white photographs of the research team and blast furnace testing stations.
Keywords: Technical reports; Tennessee Valley Authority; Phosphatic fertilizers; Phosphate mines and mining; Blast furnaces; United States. Bureau of Chemistry